Sir Richard Francis Burton Reconsidered and His Travels to Slovenian Lands - Igor Maver (Acta Neophilologica, 2018)
Sir Arnold Wilson delivered a lecture before the Royal Asiatic Society on 27 May 1937 in London at 74 Grosvenor Street as the Fifth Burton Memorial Lecture. Regardless of the fact that Burton was indeed an orientalist and an exponent of the British Empire, he nonetheless often challenged many aspects of the dominant British ethnocentrism of his day and decided to ’go native’ and get thus immersed into and possibly become part of the culture of the then Other. In his texts he sometimes openly critized the colonial policies and practices of the British Empire, which can be seen also in the selection of Burton’s extracts of texts presented at the Fifth Memorial Lecture discussed here. The article also brings the descriptions of his travels to Lipica on Slovenian ground within the Austro-Hungarian empire.